ANALISIS PERLINDUNGAN WANITA DALAM UNDANG-UNDANG PERKAWINAN TERKAIT PASAL PEMERKOSAAN DALAM PERNIKAHAN YANG SAH - Ikramina Yustika Barito (Universitas 17 Agustus 1945 Samarinda, 2021)
AbstractMarriage is a relationship in an arrangement of living tissue and is a natural human community that has been reduced to be shown to perpetuate offspring which will later form a family. Marriage is a covenant or agreement that is very serious, strong, contains transcendental values, carried out consciously by men and women to form a family whose implementation is based on willingness and agreement between the two parties. This study uses normative juridical research also called doctrinal law research.